MENINGKATKAN KETERAMPILAN MENULIS CERPEN MELALUI IKLAN TELEVISI PADA SISWA KELAS IX-A SMP NEGERI 3 BALIKPAPAN - Hj. Eny Wahyuni (Center of Language and Cultural Studies, 2015)
The purpose of this study is to see the effectiveness of TV adverts to improve ability on writing short story. Adversts broadcast in TV are used as exposures and writing short story is the focus of learning object. The study uses classroom action research as the research design and assigns the nineth grade students of SMPN 3 Balikpapan as the subject. The study is conducted in two cylcles with two meeting each. The study reveals that adverts as the media is effective to teach short story. Learning activities indicate enthusiasm and students are eager to learn. The activities increase from cycle I and achieve optimum result on cycle II. The result of achievement in the cycles is also satisfied that raise significantly from cycle I to cycle II. The study evidently reveals that TV adverts are meaningful to improve ability to write short story.